Evaluation of sexual function and vaginal prolapse relapse in patients undergoing laparoscopic sacropexy versus pectopexy - Herrmann, Mónica Isabel; Grüne, Britta; Sütterlin, Marc; Berlit, Sebastian; Wenk, Maren (In vivo, 2025)
Background/Aim: This study aimed to compare sexual function and clinical outcomes in patients undergoing laparoscopic sacropexy (LSP) versus laparoscopic pectopexy (LPP) to treat vaginal cuff or uterine prolapse. - Patients and Methods: A cross-sectional explorative cohort study of 46 patients who underwent LSP (n=23) or LPP (n=23) in our tertiary care hospital was conducted. The patients’ postoperative sexual function was evaluated (female sexual function index, FSFI), and prolapse stages were determined with the pelvic organ prolapse quantification system (POP-Q). - Results: Both groups showed comparable baseline parameters. Mean age was higher in the LSP group (66.76 vs. 61.30 years, p=0.14). The operation time was slightly longer in the LPP group (118 vs. 109 min, p=0.12). Uterus preservation was more common in LPP (p=0.02). There were a few low-grade complications [two patients LPP, one patient LSP, Clavien-Dindo-Classification (CDC) I and II, p=1.00], but no complications of ≥CDC III. Postoperative POP-Q results were comparable for both groups (p>0.05 in all parameters). The FSFI showed similar postoperative results in both groups with a slightly higher total score for the LPP cohort, even though not significant (1.60 vs. 1.40 LSP vs. LPP cohort; p=0.35). A multiple linear regression analysis was performed, however no factors influencing postoperative sexual function were identified. - Conclusion: A comparable efficacy of apical fixation was found for LSP and LPP, complications were low in both groups, and the FSFI-results were comparable with slightly better results in the LPP group. Therefore, LPP seems to be a viable and safe alternative in the treatment of POP.